2012
DOI: 10.1255/jnirs.993
|View full text |Cite
|
Sign up to set email alerts
|

In-Stream Measurement of Canola (Brassica Napus L.) Seed Oil Concentration Using in-line near Infrared Reflectance Spectroscopy

Abstract: Natural variation in the seed oil concentration of oilseed crops sent to a crushing plant can impair the recovery of the oil from the seed. Consequently, there is interest in applying in-line near infrared (NIR) spectroscopy to measure the oil concentration of the seed to be processed and, in using the information obtained, to maximise expeller efficiency. The objective of this study was to determine how well in-line NIR spectroscopy could determine the seed oil concentration of canola (Brassica napus L.) when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Non-destructive successful NIR applications to measure oil in seed have been published so far for several oilseed crops [11,[28][29][30][31]. Those cultivars are grown primarily for their rich seed oil content, which ranges from about 20% of the seed weight for soybeans to over 40% for sunflower and rapeseed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-destructive successful NIR applications to measure oil in seed have been published so far for several oilseed crops [11,[28][29][30][31]. Those cultivars are grown primarily for their rich seed oil content, which ranges from about 20% of the seed weight for soybeans to over 40% for sunflower and rapeseed.…”
Section: Discussionmentioning
confidence: 99%
“…The NIR technique has been used already in the early 1960s to detect the moisture content in seeds [10]. The charm of this methodology relies greatly on its uncomplicated sample presentation; it is a fast (a single measurement takes only a few seconds), non-destructive and reagent-free methodology, with levels of precision comparable to the primary reference methods and easily adaptable to industrial measurements [11,12]. Over the years, the NIR applications in agriculture have slowly, but steadily, been spreading and are nowadays well established in the seed sector for determining protein, moisture, and oil content [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The oil content in the grains varied between hybrids and between sowing dates (Table 3). This behavior was expected because the oil concentration of canola seeds is influenced by the genotype (TOMM et al, 2009b) and by environmental factors (LONG et al, 2012), such as temperature and rainfall (TOMM et al, 2009a).…”
Section: Near-infrared (Nir) Spectroscopymentioning
confidence: 98%
“…Additional work has shown the usefulness of NIRS in predicting features of canola seed [27] and/or meal [28]. Long et al [29] found that NIRS could measure the oil content of canola seed prior to crushing. Wittkop et al [30] used NIRS to predict NDF, ADF, and ADL in intact seed of various genotypes of oilseed rape (Brassica napus L.).…”
Section: Correlation Between Laboratory Reference Measurements and Nimentioning
confidence: 99%